Beef Production in the Flint Hills - Mike Beam (Symphony in the Flint Hills, 2010)
The Flint Hills provide an integral source of sustainable and productive forage for over 1 million head of cattle on an annual basis.
Keywords: cows; cattle; cowboy; grazing; forage; sustainable; production; beef; ranchers; ranch; processing; consumer; milk; calves